Design of automatic control system of hydraulic winch - WEN Yi; ZHANG Yaocheng (Gong-kuang zidonghua, 2018)
At present, most of hydraulic winches adopt open-loop manual control and simple PID closed-loop control method, operation smoothness of the hydraulic winch depends on the driver's experiences, so as to cause low automation degree of the winch and great working intensity for operators. In order to solve the above problems, a kind of automatic control system of hydraulic winch was designed. The system uses coordinated control between single-chip microcomputer and PID controller to adjust speed of the hydraulic winch. The single-chip microcomputer can automatically judge running state of the winch after receiving target speed, and then control opening of hydraulic valve; by splitting the target speed, the single-chip microcomputer can automatically adjust the speed of drum to the target speed with collaborative PID controller, which improves automation level of operation of the winch. The simulation results verify reliability of the system.